2019
DOI: 10.1002/wmh3.297
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation Tool for National‐Level Pandemic Influenza Planning

Abstract: The historical threat of pandemic influenza and the circulation of novel influenza viruses have led countries to strengthen their efforts in pandemic influenza preparedness planning. A cornerstone of these efforts is the creation of a comprehensive national plan that addresses all of the capacities required to prevent, detect, and respond to novel influenza outbreaks. In 2017 and 2018, the World Health Organization issued updated guidance for national pandemic planning efforts, based on lessons learned from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
2
9
0
1
Order By: Relevance
“…Accordingly, it was found that the individuals' level of depression increased as their level of anxiety increased, and their anxiety and depression levels increased when they encountered a COVID patient or had a relative with COVID. This situation coincides with the literature data suggesting that depression and anxiety are usually seen together 4,24 , and depression is triggered after anxiety 24 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Accordingly, it was found that the individuals' level of depression increased as their level of anxiety increased, and their anxiety and depression levels increased when they encountered a COVID patient or had a relative with COVID. This situation coincides with the literature data suggesting that depression and anxiety are usually seen together 4,24 , and depression is triggered after anxiety 24 .…”
Section: Discussionsupporting
confidence: 92%
“…In the studies, depression was detected by 41.2% and anxiety by 36.4% in the participants. In the literature, it has been reported that the co-occurrence rates of these two diseases are high, they trigger each other and generally develop due to common causes [2][3][4]24 . Similarly, depression and anxiety accompanied each other in the study and their incidence was found to be very high.…”
Section: Discussionmentioning
confidence: 99%
“…A dynamical study seems to be the natural sequence of this approach, as well as the production of inference models. This methodology can be applied to further data sets such as countries, cities, provinces or districts in order to help authorities and governmental agencies to improve their actions to fight the pandemic 12 .…”
Section: Resultsmentioning
confidence: 99%
“…Agencies can use previous guidelines as data points in evaluating their processes and develop updates relevant to changing institutional environments. 7…”
Section: Lessons Learned From 2009mentioning
confidence: 99%